Psychology of Decision-making: A Comparative Analysis Between Cognitive and Behaviorist Approaches to the "Asian Disease Problem" - Foka-Kavalieraki, Yulie (Neusis, 2025)
The psychology of decision-making examines the mechanisms driving human choices under conditions of uncertainty. This paper provides a comparative analysis of cognitive and behaviorist approaches, focusing on Tversky and Kahneman’s (1981) classic “Asian Disease” problem. The cognitive approach, grounded in Prospect Theory and dual-process models of thinking (System 1 and System 2), attributes the observed framing effects to cognitive biases and heuristics, resulting in systematic violations of rational decision-making. Conversely, the behaviorist approach, based on the experimental analysis of behavior, emphasizes the role of learning history and environmental stimuli that shape choices as operant responses. Experimental results obtained from postgraduate students demonstrate that preferences significantly change depending on the framing context (gains vs. losses), although differences are not always statistically significant. The paper concludes that these theoretical frameworks are complementary: cognitive psychology offers descriptive insights into mental processes and deviations from rationality, whereas the behaviorist perspective provides causal explanations connecting behavior with learning experiences and environmental reinforcements. The synthesis of these approaches is essential for a comprehensive understanding of the complex processes underlying human decision-making.